PROJECTION OF THE 7Li WAVE FUNCTION IN THE (dn)α- AND(αd)n-MODELS ON THE 6Liαd+ n CLUSTER CHANNEL - Afanasyeva, N.V.; Burkova, N.A.; Zhaksybekova, K.A.; Urazalin, A.A. (Recent Contributions to Physics, 2011)
Within the three-body α dn -model for 7Li nucleus the Li + n relative-motion wave functions have been obtained and spectroscopic Sn -factors of neutron separation has been calculated.